Characterization of Rhizobium grahamii extrachromosomal replicons and their transfer among rhizobia - Althabegoiti, Maria Julia (2014)
Background: Rhizobium grahamii belongs to a new phylogenetic group of rhizobia together with Rhizobium mesoamericanum and other species. R. grahamii has a broad-host-range that includes Leucaena leucocephala and Phaseolus vulgaris, although it is a poor competitor for P. vulgaris nodulation in the presence of Rhizobium etli or Rhizobium phaseoli strains. This work analyzed the genome sequence and transfer properties of R. grahamii plasmids. Results: Genome sequence was obtained from R. grahamii CCGE502 type strain isolated from Dalea leporina in Mexico. The CCGE502 genome comprises one chromosome and two extrachromosomal replicons (ERs), pRgrCCGE502a and pRgrCCGE502b. Additionally, a plasmid integrated in the CCGE502 chromosome was found. The genomic comparison of ERs from this group showed that gene content is more variable than average nucleotide identity (ANI). Well conserved nod and nif genes were found in R. grahamii and R. mesoamericanum with some differences. R. phaseoli Ch24-10 genes expressed in bacterial cells in roots were found to be conserved in pRgrCCGE502b. Regarding conjugative transfer we were unable to transfer the R. grahamii CCGE502 symbiotic plasmid and its megaplasmid to other rhizobial hosts but we could transfer the symbiotic plasmid to Agrobacterium tumefaciens with transfer dependent on homoserine lactones. Conclusion: Variable degrees of nucleotide identity and gene content conservation were found among the different R. grahamii CCGE502 replicons in comparison to R. mesoamericanum genomes. The extrachromosomal replicons from R. grahamii were more similar to those found in phylogenetically related Rhizobium species. However, limited similarities of R. grahamii CCGE502 symbiotic plasmid and megaplasmid were observed in other more distant Rhizobium species. The set of conserved genes in R. grahamii comprises some of those that are highly expressed in R. phaseoli on plant roots, suggesting that they play an important role in root colonization.